Content validation of Occupational Health & Safety Monitoring Questionnaire (OHSMQ) for occupational stress risk assessment among port terminal workers - Yaakub, Norwahida; Ranjan, Mokhtar Zamimi; Baharudin, Mohd Rafee; Mohd Elias, Saliza; Zainuddin, Huda; Mohd Noor, Mohd Azhar (Penerbit Akademia Baru, 2019)
Exposure to occupational stress is escalating in the working environment. Occupational stress directly or indirectly eclipses many other hazards and contributes to ill health. The Occupational Health & Safety Monitoring Questionnaire (OHSMQ) was developed for use in a port terminal setting. The objective of this paper is to present the process of construction and content validity of the OHSMQ’s items in order to conduct Occupational Safety & Health (OHS) control modification for occupational stress risk assessments among port terminal workers. The content validity process involved the act of conceptualisation, development, and validation. The process began with a literature review (adopt and adapt) and expert panel’s judgement on the item development process. A list of 20 items was then developed. Its content validation was rated by a panel of fifteen experts. This paper demonstrated the initial phase of scale development for the OHSMQ items. This newly developed item allows the integration of OHS factors during several OHS management activities as constructed through the review and judgement process by a panel of experts in the field. 20 items were deemed acceptable to be passed on to the next stage of data collection. The items’ content validity (I-CVI) measurement was within an acceptable range of more than 0.75. The scale’s content validity (S-CVI) had an excellent score of 0.95. The study findings show that the Occupational Health & Safety Monitoring Questionnaire (OHSMQ) is valid and has good structural characteristics. Content validity ensures accurate interpretation of results. In order to support the construct validity of an instrument, documenting findings from content validity is therefore essential.